PRospective Evaluation of natriuretic peptide-based reFERral of patients with chronic heart failure in primary care (PREFER): a real-world study - Hobbs, FR; Hussain, RI; Vitale, C; Pinto, YM; Bueno, H; Lequeux, B; Pauschinger, M; Obermeier, M; Ferber, PC; Gustafsson, F (BMJ Publishing Group, 2021)
Objective To assess current management practice of heart failure with reduced ejection fraction (HFrEF) in multinational primary care (PC) and determine whether N-terminal-pro-B-type natriuretic peptide (NT-pro-BNP)-guided referral of HFrEF patients from PC to a cardiologist could improve care, defined as adherence to European Society of Cardiology (ESC) guideline-recommended pharmacotherapy.